Establishment of reference intervals for bone turnover markers in healthy Chinese older adults - Li-Li Sun; Rong-Rong Cao; Jin-Di Wang; Guo-Long Zhang; Fei-Yan Deng; Shu-Feng Lei (Taylor & Francis Group, 2023)
Background Reference ranges for bone turnover markers (BTMs) are still lacking in the healthy Chinese population. Aim To establish reference intervals for BTMs and to investigate the correlations between BTMs and bone mineral density (BMD) in Chinese older adults. Subjects and methods A community-based cross-sectional study was conducted among 2511 Chinese subjects aged over 50 yrs residing in Zhenjiang, Southeast China. Reference intervals for BTMs (i.e. procollagen type I N-terminal propeptide, P1NP; β cross-linked C-terminal telopeptide of type I collagen, β-CTX) were calculated as the central 95% range of all measurements in Chinese older adults. Results The reference intervals of P1NP, β-CTX and P1NP/β-CTX were 15.8-119.9 ng/mL, 0.041-0.675 ng/mL and 49.9-1261.5 for females and 13.6-111.4 ng/mL, 0.038-0.627 ng/mL and 41.0-1269.1 for males, respectively. In the multiple linear regression analysis, only β-CTX was negatively associated with BMD after adjusting for age and body mass index (BMI) in both sex-stratified groups (all p < .05). Conclusion This study established age- and sex-specific reference intervals for BTMs in a large sample of healthy Chinese participants ≥ 50 and < 80 years of age and explored the correlations between BTMs and BMD, which provides an effective reference for the assessment of bone turnover in the clinical practice of osteoporosis.